2007
DOI: 10.1007/s11423-007-9033-x
|View full text |Cite
|
Sign up to set email alerts
|

Cultural competence and instructional design: Exploration research into the delivery of online instruction cross-culturally

Abstract: The amount of resources being poured by Western universities, companies, and governments into creating educational content to be exported (via the Internet) to other cultures is astounding. Those assigned to accomplish this task are left with the great challenge of meeting the needs of learners who come from cultures that are foreign to them, and who often have very different abilities and expectations than originally assumed. This study explores the cultural competence in the lived experience of 12 profession… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
107
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(111 citation statements)
references
References 15 publications
3
107
0
1
Order By: Relevance
“…Thus, as an increasing number of minority students continue to enroll in online education (Ashong & Commander, 2012;Petersen, 2015), it is imperative that researchers examine the extent to which instructional strategies such as collaborative learning-well documented in the research literature as effective for the general online student population-works effectively for culturally diverse students. This is particularly important because several studies have reported that instructors of online courses often fail to recognize and address the cultural diversity of their learners in the online learning environments (e.g., Adeoye & Wentling, 2007;Gunawardena, Layne, & Frechette, 2012;Mushtaha & Troyer, 2007;Rogers, Graham & Mayes, 2007), and results from some studies seem to suggest that students from diverse cultural backgrounds exhibit poor leadership skills in leading online discussion (Okwumabua, Walker, Hu, & Watson, 2011), as well as experience challenges in participating online collaborative learning activities (Du & Anderson, 2003). The purpose of this study, therefore, was to investigate the perceptions of culturally diverse graduate students about online collaborative learning activities.…”
Section: Online Collaborative Learning Activities: the Perceptions Ofmentioning
confidence: 99%
“…Thus, as an increasing number of minority students continue to enroll in online education (Ashong & Commander, 2012;Petersen, 2015), it is imperative that researchers examine the extent to which instructional strategies such as collaborative learning-well documented in the research literature as effective for the general online student population-works effectively for culturally diverse students. This is particularly important because several studies have reported that instructors of online courses often fail to recognize and address the cultural diversity of their learners in the online learning environments (e.g., Adeoye & Wentling, 2007;Gunawardena, Layne, & Frechette, 2012;Mushtaha & Troyer, 2007;Rogers, Graham & Mayes, 2007), and results from some studies seem to suggest that students from diverse cultural backgrounds exhibit poor leadership skills in leading online discussion (Okwumabua, Walker, Hu, & Watson, 2011), as well as experience challenges in participating online collaborative learning activities (Du & Anderson, 2003). The purpose of this study, therefore, was to investigate the perceptions of culturally diverse graduate students about online collaborative learning activities.…”
Section: Online Collaborative Learning Activities: the Perceptions Ofmentioning
confidence: 99%
“…Koul and Kanwar (2006) stated that at IGNOU, the courses are designed keeping in mind the established quality assurance practices and principles. Rogers et al (2007) found that instructional designers" or instructors" awareness of the potential differences between cultures does not necessarily mean this knowledge is integrated into the design of online courses. Krishnapillai (2011) discussed about the benchmarks to be followed in open universities regarding face-to-face classes as learning package contain the schedule for face-to-face classes.…”
Section: Issn: 2320-5407mentioning
confidence: 99%
“…In these collections, scholars and practitioners reflect on the use of instructional design practices across sectors and across borders and provide insight on lessons learned and challenges faced. Rogers, Graham and Mayes (2007) interviewed 12 instructional designers about their experiences creating online instruction for people of other cultures. In response to their question about importance placed on cultural differences, these barriers emerged:…”
Section: Culture and The Instructional Design Processmentioning
confidence: 99%
“…The findings of this study show that these elements of culture are pervasive and impactful in content decisions; however, this research design also allowed for discovery of several additional elements of the culture of all stakeholders that interact frequently and significantly with all learner-centered decisions. Rogers, Graham and Mayes (2007) found that instructional designers designing for other cultures place less emphasis on context and experiences of learners and focus more on content. The findings of this study suggest a need for models that prompt designers to consider culture beyond language and communications.…”
Section: Cultural Interactions With Balancing the Needs Of Stakeholdersmentioning
confidence: 99%